Compaction trends of full stiffness tensor and fluid permeability in artificial shales. Issue 3 (29th November 2017) - Beloborodov, Roman; Pervukhina, Marina; Lebedev, Maxim
Summary: We present a methodology and describe a set-up that allows simultaneous acquisition of all five elastic coefficients of a transversely isotropic (TI) medium and its permeability in the direction parallel to the symmetry axis during mechanical compaction experiments. We apply the approach to synthetic shale samples and investigate the role of composition and applied stress on their elastic and transport properties. Compaction trends for the five elastic coefficients that fully characterize TI anisotropy of artificial shales are obtained for a porosity range from 40 per cent to 15 per cent. A linear increase of elastic coefficients with decreasing porosity is observed. The permeability acquired with the pressure-oscillation technique exhibits exponential decrease with decreasing porosity. Strong correlations are observed between an axial fluid permeability and seismic attributes, namely, VP / VS ratio and acoustic impedance, measured in the same direction. These correlations might be used to derive permeability of shales from seismic data given that their mineralogical composition is known.